Factors on deciding TVET for first choice educational journey among pre-secondary school student - Omar, Mohd Khaizer; Rauf, Md Abdur; Ismail, Normala; Mat Rashid, Abdullah; Mohd Puad, Mohd Hazwan; Zakaria, Anis (Ubiquity Press, 2020)
Less was known about predicting factors concerning students’ knowledge, interests, and motivation towards Technical and Vocational Education and Training (TVET). The study aimed to determine the relationships among pre-secondary school students’ demographic factors, knowledge possession, interest and motivation related to TVET stream and to identify the relationship between informational methods and knowledge possession, interest and motivation of students towards TVET. A quantitative descriptive study used to determine the factors contributing to student’s knowledge, interests, and motivation, which play a critical role in 64 pre-secondary school students’ choice of TVET. A questionnaire was utilized to determine the participants’ perceptions of choosing the TVET field. Descriptive and inferential statistics, including one-way ANOVA analysis, were used to analyze the data. Findings revealed that information delivery methods such as receiving information from teachers, parents, peers, internet platforms with motivation have a significant relationship for students to choose TVET. Thus, the promotion and strategy on empowering TVET is salient and developing a positive image on TVET will encourage myriad stakeholders on the importance of TVET for the nation. It is a high time to rebrand the image of vocational education as an element to train skilled human capital development.